UMKM Kota Tangerang Go Digital: Branding Efektif dan Peta Bisnis Menuju Usaha Naik Kelas - Hadiwijaya, Dudung; Pratama, Putra; Rosidi, Imron (Jaanur ElBarik Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) form the backbone of Tangerang City's economy, with a significant increase in business numbers over the past five years. However, this quantitative growth has not been matched by improvements in branding and digital visibility—two essential components for competitiveness in the digital era. Many MSMEs still struggle to create professional visual identities and remain invisible to local consumers in online searches. This community service initiative was conducted in Juru Mudi Village, Tangerang City, involving 30 MSMEs from the service, handicraft, and culinary sectors. The program aimed to address these challenges by focusing on two key areas: (1) designing visual identities and promotional materials using the Canva platform, and (2) optimizing business visibility through Google Maps for Business. The workshop employed an interactive format combining theoretical presentations, case studies, and hands-on practice. These findings demonstrate the effectiveness of practical, tool-based training in enhancing MSMEs’ brand image and local market reach. The program highlights the potential of accessible digital platforms to empower small businesses toward sustainable digital transformation.